Peculiarities of Psychomotor Reaction of Schoolchildren with Intellectual Disabilities: Aspects of Moderate Intensity Exercising and Age - Dovilė Selickaitė; Diana Rėklaitienė; Jūratė Požėrienė (Lithuanian Sports University, 2018)
Background. Intellectual disability is defined as significantly reduced ability to understand new or complex information, to learn and to apply new skills. Integration into the society and independent living for intellectually disabled people is demanding because of slowdown decision processing. Quick enough response time is of vital importance not only for the motor development but also for faster and better adaptation to the changing life conditions.   Methods. The  subjects  were  112  persons  with  and  without  intellectual  disability  aged  11  to  18  years  and recruited for the study. The Reaction Timer RA-1 was used to measure reaction time and to determine the speed characteristics  of  the  person's  psychomotor  response  before  and  after  moderate  intensity  exercising.  Heart  rate monitor Polar RS800 was used to measure the person's heart rate. Results. The best reaction time was demonstrated by 16-year-old normally developed individuals and those with mild intellectual disability (p < .05). The slowest were 11 and 12-year-old individuals (p < .05). The best reaction time was demonstrated by 14-year-old individuals with moderate intellectual disability and the worst - by 12 and 16 year-old persons with this disability (p < .05). Conclusion. Moderate-intensity exercising has a positive influence on the execution of the complex reaction task (LRHL). The considerable reaction time increase was observed for individuals with moderate intellectual disability. Keywords: intellectual disability, reaction time, moderate intensity exercising.